2019
DOI: 10.1182/blood-2019-131805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optimal Thalassemia Screening Strategies for Migrant Populations in Thailand: A Mixed-Methods Approach

Abstract: BACKGROUND: Severe thalassemia is common in Southeast Asia (SEA) and can lead to transfusion dependent anemia, growth retardation, and perinatal death. Prevention and control of thalassemia can be approached either preconceptionally (through carrier screening, reproductive planning, or preimplantation diagnosis) or antenatally (through prenatal screening and diagnosis and termination of pregnancy). Thailand's national thalassemia program focuses on antenatal interventions, provided free to citizens. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Accordingly, low-cost or free of charge services were identified as facilitators [13,60,82]. Studies also found that lack of health information or health system understanding as well as poor health-literacy reduced access to health care [17,27,31,39,44,55,[66][67][68]78,80,81,83,84,91,95,105,109,110]. Complementary, information, staff communication, knowledge and perceived risk as well as school and health education were stated to increase access [16,51,69,100].…”
Section: Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, low-cost or free of charge services were identified as facilitators [13,60,82]. Studies also found that lack of health information or health system understanding as well as poor health-literacy reduced access to health care [17,27,31,39,44,55,[66][67][68]78,80,81,83,84,91,95,105,109,110]. Complementary, information, staff communication, knowledge and perceived risk as well as school and health education were stated to increase access [16,51,69,100].…”
Section: Accessibilitymentioning
confidence: 99%
“…Many studies focused on barriers and some on contributors to accessibility from the perspective of migrants. One often cited barrier was affordability or high cost [42,43,49,55,65,69,77,81,83,[104][105][106][107][108]. Accordingly, low-cost or free of charge services were identified as facilitators [13,60,82].…”
Section: Accessibilitymentioning
confidence: 99%
See 2 more Smart Citations